Penyalahgunaan Fungsi Trotoar oleh Pedagang Kaki Lima di Pasar Bojong Kecamatan Kedungwaringin Kabupaten Bekasi Dihubungkan dengan Peraturan Daerah Kabupaten Bekasi Nomor 4 Tahun 2012 Tentang Ketertiban Umum - Dewi Fitri Yani; Hana Farida (Wajah Hukum, 2021)
Sidewalks are pedestrian paths that are generally parallel to and / or higher than the surface of the pavement to ensure pedestrian safety. However, the increasing number of street vendors competing to get land for trading causes street vendors to use sidewalks to enter their trading areas. This of course is not in accordance with the use and function of the sidewalk. So that the authors are interested in studying the causes of the rise of street vendors who misuse the function of the sidewalk. The research method used in this paper is to use normative juridical, where data collection techniques are researched through literature studies, law books, and other literature. the sidewalk bridge in Bojong Village which causes traffic jams for motorcyclists and pedestrians who pass by every morning. This of course can create a severe traffic jam and increasingly slum because at this location in addition to the market and the large number of street vendors, the large number of public transportation stops to attract passengers and heavy vehicles that also pass through this area.